Burnout, Depression, and Borderline Personality: A 1,163-Participant Study - Bianchi, Renzo; Rolland, Jean-Pierre; Salgado, Jesús F. (Frontiers in Psychology, 2018)
We examined the association of burnout with borderline personality (BP) traits in a study of 1,163 educational staff (80.9% women; mean age: 42.96). Because burnout has been found to overlap with depression, parallel analyses of burnout and depression were conducted. Burnout symptoms were assessed with the Shirom-Melamed Burnout Measure, depressive symptoms with the PHQ-9, and BP traits with the Borderline Personality Questionnaire. Burnout was found to be associated with BP traits, controlling for neuroticism and history of depressive disorders. In women, burnout was linked to both the “affective insecurity” and the “impulsiveness” component of BP. In men, only the link between burnout and “affective insecurity” reached statistical significance. Compared to participants with “low” BP scores, participants with “high” BP scores reported more burnout symptoms, depressive symptoms, neuroticism, and occupational stress and less satisfaction with life. Disattenuated correlations between burnout and depression were close to 1, among both women (.91) and men (.94). The patterns of association of burnout and depression with the main study variables were similar, pointing to overlapping nomological networks. Burnout symptoms were only partly attributed to work by our participants. Our findings suggest that burnout is associated with BP traits through burnout-depression overlap.